Er:YAG pre-Treatment for bonding of orthodontic bracket: 1 year of in vitro treatment - De Jesus Tavarez, Rudys Rodolfo; Bezerra, Gisele Lima; De Souza Penha, Karla Janilee; Torres, Carlos Rocha Gomes [UNESP]; Firoozmand, Leily Macedo (Taylor & Francis, 2017)
Objective: The aim of this study was to evaluate in vitro bond strength of metal brackets bonded with: Total etch, total etch with erbium: yttrium aluminum garnet laser (Er:YAG) and self-etching adhesive systems, submitted to thermal-mechanical cycling, simulating 1 year of orthodontic treatment. Materials and methods: For the study, 80 bovine incisors were randomly divided into 3 experimental groups (n=16 each): XT-Acid etching +Transbond XT, XT/Er:YAG-Transbond XT associated with Er:YAG laser irradiation (λ2.94 μm, 60 mJ, 10 Hz) and SEP-Transbond Plus Self Etching Primer. Samples were submitted to thermal-mechanical cycling, simulating 1 year of orthodontic treatment. Afterward, the shear bond strength test was performed in a universal test machine at a speed of 0.5mm/min. Samples were evaluated under a stereomicroscope and by scanning electron microscopy for analysis of enamel surface and adhesive remnant index. Data were analyzed using Kruskal-Wallis and Mann-Whitney (with Bonferroni correction) statistical tests. Results: Statistically significant difference was observed between the groups studied (p<0.05). Groups XT and SEP showed the highest bond strength values, without statistical difference between them, while group XT/Er:YAG showed reduction in bond strength values. Higher frequency of adhesive failures between enamel and adhesive system was verified for groups XT and XT/Er:YAG. Conclusion: The conventional (XT) and self-etching (SEP) adhesive systems showed mean bond strength values, similar between them, whereas the previous application of Er:YAG laser promoted the lowest bond strength values.
Keywords: Dentin-bonding agents; Enamel; Orthodontic bonding; Orthodontic brackets; Self-etching adhesive system; Shear strength; Yag laser